2021
DOI: 10.1097/rhu.0000000000001348
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Choroid Thickness as a Marker of Systemic Inflammation in Patients With Ankylosing Spondylitis

Abstract: Background and ObjectiveAnkylosing spondylitis (AS) is an inflammatory disease, and choroidal thickness (CT) has been proposed and evaluated as a potential marker of systemic inflammation associated with AS and other inflammatory diseases. This study compared CT measurements taken from patients with severe AS disease activity without eye inflammation with those taken from healthy subjects.MethodsThis cross-sectional, multicenter study compared CT in 44 patients with high AS disease activity, and no history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Platelet parameters have been suggested as important markers of inflammation ( Bilen et al, 2015 ; Kalelioglu et al, 2015 ; Akboga et al, 2016 ; Koupenova et al, 2018 ). Unlike other rheumatic disease such as SLE and Sjögren’s syndrome (SjS), AS is a rheumatic disease characterized by serious inflammatory responses ( Vanaki et al, 2018 ; Vinker Shuster et al, 2018 ; Steiner et al, 2020 ). It has been clear that inflammation has a crucial role in the development of AS ( Machado et al, 2016 ; Tseng et al, 2016 ; Ranganathan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet parameters have been suggested as important markers of inflammation ( Bilen et al, 2015 ; Kalelioglu et al, 2015 ; Akboga et al, 2016 ; Koupenova et al, 2018 ). Unlike other rheumatic disease such as SLE and Sjögren’s syndrome (SjS), AS is a rheumatic disease characterized by serious inflammatory responses ( Vanaki et al, 2018 ; Vinker Shuster et al, 2018 ; Steiner et al, 2020 ). It has been clear that inflammation has a crucial role in the development of AS ( Machado et al, 2016 ; Tseng et al, 2016 ; Ranganathan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ankylosing spondylitis (AS) is a chronic autoimmune inflammatory disease that primarily invades the spine and involves the cuboid iliac joint (1). The disability rate of patients with AS is high and AS has a serious impact on quality of life (2,3). Studies have shown that AS is associated with genetics, infection, immunity, inflammatory cell infiltration, cytokine imbalance and other factors (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…9 Patients with AS without eye inflammation and high disease activity have a significantly thicker choroid than healthy subjects. 10 In this study, we hypothesized that CT decreases after biological treatment, therefore acting as a marker of systemic inflammation in patients with AS. This study aimed to compare CT in biological treatment-naive disease-active patients before and after 6 months of therapy.…”
mentioning
confidence: 99%
“…Patients with AS without eye inflammation and high disease activity have a significantly thicker choroid than healthy subjects 10 …”
mentioning
confidence: 99%